Emotional intelligence as a buffer of occupational stress. Issue 5 (1st August 2016) - Newton, Cameron J; Teo, Stephen; Pick, David; Ho, Marcus; Thomas, Drew
Abstract : Purpose: The purpose of this paper is to examine the role of emotional intelligence (EI) as a buffer to job stressors on employee adjustment. Design/methodology/approach: Based on the Job Demands Resources Model, this study examined 306 nurses in the healthcare sector to test a model of job stressors, EI, and their interactions nursing adjustment outcomes (i.e., job satisfaction and psychological health). The hypothesized model predicted that higher trait emotional intelligence would act as a buffer to the potential negative effects of stressors on employee adjustment. Two-way moderated hierarchical multiple regression analyses was used to test the model in addition to interaction effects. Findings: The results of this study revealed mixed results in terms of the expected main effects of EI and the five significant moderating effects. While some interactions support a buffering hypothesis; contrary to expectations, a buffering effect was also found for those with low EI. Research limitations/implications: The findings enable a better understanding how EI moderates the effects of stressors on important work outcomes in healthcare. Additionally, the implications from this study allows healthcare administrators and managers to improve staffing and work outcomes through identifying and selecting staff who are characterised by higher trait EI or alternatively, train staff in self-awareness and dealing with emotional behaviours. Practical implications: HR managers could focus on selecting staff, who possessed higher trait EI for roles where overload and ambiguity are endemic to the job performed. Training could also be used to enhance EI among managers to focus on self-awareness and dealing with emotional behaviors. Originality/value: This study makes several contributions to understanding how EI moderates the relationships between work stressors and workplace adjustment and wellbeing.